Prevalence of hyperemesis gravidarum and associated risk factors among pregnant women in a tertiary health facility in Northeast, Nigeria - Aminu, Muhammad B.; Alkali, Mohammed; Audu, Bala M.; Abdulrazak, Toyin; Bathna, Dauda (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: One of the commonest symptoms observed in pregnant women before the 20th week of gestation is nausea and vomiting, an exaggeration of these symptoms hyperemesis gravidarum (HEG) could result in maternal and fetal catastrophes and even death. The objective of this study was to determine the prevalence and associated risk factors for hyperemesis gravidarum among pregnant women at booking. Methods: A prospective institutional based study design was done among 452 pregnant women seen at booking in a tertiary hospital in Northeast Nigeria from the 1st February 2019 to 30th June 2019. Data was summarized using descriptive statistics. OR was used to measure significant risk. Results: The observed prevalence of hyperemesis gravidarum among pregnant women in the study is 44.9%. The Majority (81.4%) of these women were between the age range of 21 and 35 years. Mean age of 27 years. Multiparity (33.4%), previous (44.9%) and family history of HEG (31.6%) were identified as important risk factors for developing HEG. Grand multiparity (11.5%) and gestational age less than 13 weeks (6.64%) were however less likely observed to be risks for HEG. Conclusions: HEG is a common problem in pregnancy with almost half of the number of pregnant women at booking affected. Multiparity and past history of HEG are pointers to developing the condition and it should be looked out for among at risk group of pregnant women, so that early intervention can be instituted to avoid any possible adverse outcome.